Pendampingan UMKM Opak melalui Inovasi Kemasan, Pemasaran Digital, dan Pemanfaatan Limbah Kulit Singkong menjadi Pupuk Organik Cair (POC) di Dusun Tegal Jaya, Desa Batumarta I - Ali Junior Niku Al’basit; Yogi Sopiansyah; Riyan Andika; Gisella Putri; Enda Yuni Aulia; Sulia Ningsih (CV. ITTC INDONESIA, 2026)
Opak Micro, Small, and Medium Enterprises (MSMEs) in Tegal Jaya Hamlet, Batumarta I Village, have significant economic potential, but still face various obstacles, particularly in product packaging, marketing, and waste management. This mentoring activity aims to increase the competitiveness of opak MSMEs through packaging innovation, digital marketing implementation, and the utilization of cassava peel waste into liquid organic fertilizer (POC). The implementation method includes socialization, training, and direct mentoring for MSMEs. Packaging innovation is carried out to increase the selling value and attractiveness of the product, while digital marketing is implemented through the use of social media and online platforms as a promotional tool. In addition, previously unused cassava peel waste is processed into POC as an effort to reduce waste and create added value. The results of the activity indicate an increase in understanding and skills of MSMEs in product packaging, digital marketing utilization, and waste processing into useful products. This mentoring activity is expected to support the sustainability of opak MSMEs and contribute to the sustainable development of the local economy.